IMPLIKATUR PERCAKAPAN DALAM GELAR WICARA “SENTILAN SENTILUN” DI METRO TV - Wiwiek Dwi Astuti (Kandai, 2017)
Attitudes and ideas conveyed through verbal forms may not necessarily be attitudes and meanings, but can be different or even contrary to what is stated. Submission of intent is what is known as the implicature of conversation. The utterances are analyzed to describe (1) the function of the conversation implicature in talk show of sentilan sentilun episode of ‘Siapa Ikut Gerobak’, and (2) the violation of cooperative principle and/politeness principle in the talkshow. ’The method used is listening and note taking. The findings related to the function of implicature is the use of representative (assertive), directive (imposive), expressive, commisive, and declarative utterance. The violation of cooperative principle with all the maxims is clearly seen in encountering and language games (joke).